Perbandingan Penokohan Larung Karya Ayu Utami dengan Perahu Kertas Karya Dewi Lestari - Nasution, Risela; R., Syahrul; Ngusman, Ngusman (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was (1) to describe the characterizations in the novel works Float Boat novel Ayu Utami and Dewi Lestari paper work. (2) Similarities and differences in the two novel characterizations. (3) The meaning of the characterizations in the second novel. The data in this study is that there are events in the novel that shows the two characterizations. The data source of this research is the novel Paper Boats Float and novels. Data were collected by way of reading, understanding, and then take stock characterizations marks contained in these two novels. The study's findings are contained in the novel characterizations Float Boat Paper 10 figures and 10 figures that have the same four roles of son, friend, lover and mother. Float child character in the novel is closed and dependent, while the character in the novel Paper Boats independent and not dependent. Role as a friend of the novel character Float cool, while the character in the novel Paper Boats attention. Role as the beloved character in a novel Float resigned, while the novel Paper Boats compassionate. The role of the mother in the novel Float loving character, while the character in the novel Paper Boats patient.